National Culture and Urban Resilience: A Case Study of Resilient Cities - Cilk, Madison (Consilience, 2020)
As climate change, population growth, and globalization create new challenges for cities around the world, it is imperative that urban areas take steps to increase their resilience. Previous research has shown that national culture, or the beliefs and attitudes that guide behavior, can play a significant role in shaping the values of a nation’s citizens. With more and more cities designing urban resilience plans, it is highly relevant to assess the role that national culture plays in the creation of these plans. Through a qualitative content analysis of 71 urban resilience plans from 27 countries around the world using Geert Hofstede’s cultural dimensions theory, this research assesses whether and how national culture influences urban resilience efforts. The results of the analysis show that, for many cities, urban resilience efforts are not strongly influenced by national culture, but instead share a common thread of being inclusive, future-oriented, and prioritizing quality of life over profits.